4-Dechloro-14-deoxy-oxacyclododecindione and 14-deoxy-oxacylododecindione, two inhibitors of inducible connective tissue growth factor expression from the imperfect fungus Exserohilum rostratum. Issue 3 (1st February 2015) - Richter, Julia; Sandjo, Louis P.; Liermann, Johannes C.; Opatz, Till; Erkel, Gerhard
Graphical abstract: Abstract: Connective tissue growth factor (CTGF/CCN2), a member of the CCN superfamily of secreted cysteine-rich glycoproteins, is a central mediator of tissue remodeling and fibrosis. CTGF is suggested to be an important down-stream effector of transforming growth factor-beta (TGF-β) signaling and has therefore reached considerable pathophysiological relevance because of its involvement in the pathogenesis of fibrotic diseases, atherosclerosis, skin scarring, and other conditions with excess production of connective tissue. In a search for inhibitors of inducible CTGF expression from fungi, two new macrocyclic lactones, namely 4-dechloro-14-deoxy-oxacyclododecindione (1 ) and 14-deoxy-oxacylododecindione, (2 ) along with the previously described congener oxacyclododecindione (3 ) were isolated from fermentations of the imperfect fungus Exserohilum rostratum . The structure of the compounds were elucidated by a combination of one- and two-dimensional NMR spectroscopy and mass spectrometry. Compounds1 and2 turned out to inhibit TGF-β induced CTGF promoter activity in transiently transfected HepG2 cells in a dose-dependent manner with IC50 values of 1.8 μM and 336 nM, respectively, and also antagonized TGF-β induced cellular effects including CTGF mRNA levels, CTGF protein expression and tube formation.